Analysis of Learning Evaluation at TKIT Nurul Ilmi in Children’s Emotional Aspect - Lily Sardiani Daulay; Nurmawati Nurmawati; Ahmad Syukri Sitorus; Nur Elmi (Universitas Muhammadiyah Enrekang, 2023)
In childhood there are six areas of life development, including emotional development, so that the assessment of emotional development in children must be evaluated early. An objective assessment can properly monitor a child's emotional development. This research was conducted at TKIT Nurul Ilmi, Percut Sei Tuan District, Deli Serdang Regency. The research method used is qualitative research using interview, observation, and documentation data collection techniques. The activities used by TKIT Nurul Ilmi in developing children's emotional intelligence are playing puzzles and coloring, training queues, and getting used to sharing.